HKS Misinfo Review 2020
DOI: 10.37016/mr-2020-023
|View full text |Cite
|
Sign up to set email alerts
|

Feeling “disinformed” lowers compliance with COVID-19 guidelines: Evidence from the US, UK, Netherlands and Germany

Abstract: This study indicates that, during the first phase of the coronavirus (SARS-CoV-2) pandemic in 2020, citizens from the US, UK, Netherlands, and Germany experienced relatively high levels of mis-and disinformation in their general information environment. We asked respondents to indicate the extent to which they experienced that general information on the new coronavirus (SARS-CoV-2 and the disease it causes, COVID-19) was erroneous or inaccurate (misinformation) or intentionally misleading (disinformation). Tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 18 publications
5
54
1
1
Order By: Relevance
“…Employing a quantitative content analysis, Brennen et al (2020) found a predominance of reconfigured content, with a majority of misleading or false claims focusing on the actions or policies of public authorities, including government and international bodies like the WHO or the United Nations. Surveying Internet users in six countries in the spring of 2020, Nielsen et al report that a high number of citizens say that they came across false or misleading information about COVID-19, in particular on social media ( Nielsen et al 2020 ), a finding backed by Hameleers, van der Meer, et al (2020) in a study of four countries.…”
Section: Covid-19 Misinformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Employing a quantitative content analysis, Brennen et al (2020) found a predominance of reconfigured content, with a majority of misleading or false claims focusing on the actions or policies of public authorities, including government and international bodies like the WHO or the United Nations. Surveying Internet users in six countries in the spring of 2020, Nielsen et al report that a high number of citizens say that they came across false or misleading information about COVID-19, in particular on social media ( Nielsen et al 2020 ), a finding backed by Hameleers, van der Meer, et al (2020) in a study of four countries.…”
Section: Covid-19 Misinformationmentioning
confidence: 99%
“…Despite the proliferation of scholarship on misinformation over the last several years, and the broader observation that we live in a “visual culture” where much signification is carried out through visuals ( Evans and Hall 1999 : 2), there remain few studies of visuals in mis- or disinformation. Recent work by Hemsley and Snyder, for instance, provides a framework of how visual artifacts contribute to misinformation ( Hemsley and Snyder 2018 ) while Hameleers, Powell, et al (2020) investigate the credibility of textual versus multimodal (text-plus-visual) disinformation, finding that multimodal disinformation is considered slightly more credible than textual disinformation. Despite these examples, broader studies of visuals in misinformation remain few and far between.…”
Section: Covid-19 Misinformationmentioning
confidence: 99%
“…Such information uncertainty may as well have implications on the public’s information behaviors. In a recent study, perceived exposure to COVID-19 misinformation was positively associated with seeking more information and complying with health advisories (Hameleers et al, 2020). Because perceived misinformation exposure takes into account individuals’ judgment on the veracity of information, its implications may differ from exposure to misinformation that is based on actual state of scientific evidence (Vraga & Bode, 2020).…”
Section: The Spread Of Misinformation During a Pandemicmentioning
confidence: 99%
“…Therefore, next to the challenges, the COVID-19 pandemic also offers the unique opportunity to strengthen the role of science in public discussions and future policy decisions through proactive and transparent communication and to inform the public about the scientific process. For the COVID-19 pandemic, there is evidence that the presence of corrective information helps to debunk misinformation [van der Meer and Jin, 2020] and to increase compliance with measures [Hameleers, van der Meer and Brosius, 2020]. This indicates that the public should be transparently informed about the current state of affairs and be involved in the ongoing discussion of policy decisions, and can be trusted to act cooperatively and intelligently.…”
Section: Managing Transparencymentioning
confidence: 99%